Classical sociological theory : a reader - McIntosh, Ian, 1960- (Edinburgh : Edinburgh University Press, 1997)
A generous set of readings taken from Marx, Weber and Durkheim, deliberately lengthy to impart a full understanding of the text, are the basis of this reader that is aimed at 1st and 2nd year undergraduate students of sociological theory and social theory.
Karl Marx -- Max Weber -- Emile Durkheim.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Marx, Karl, -- 1818-1883.; Weber, Max, -- 1864-1920.; Durkheim, Émile, -- 1858-1917.; Marx, Karl, -- 1818-1883.; Weber, Max, -- 1864-1920.; Durkheim, Émile, -- 1858-1917.; Durkheim, Émile, -- 1858-1917; Marx, Karl, -- 1818-1883; Weber, Max, -- 1864-1920; Marx, Karl, -- (1818-1883); Weber, Max, -- (1864-1920); Durkheim, Émile, -- (1858-1917); Sociology -- Philosophy; Sociology -- History; Sociologie -- Philosophie; Sociologie -- Histoire; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; SOCIAL SCIENCE -- Sociology -- General; Sociology; Sociology -- Philosophy; Aufsatzsammlung; Soziologische Theorie; Sociologie; Theorieën.; Sociologie -- Histoire; Sociologie -- Philosophie; History